Al-Salaf wa al-Salafiyah fi al-Fikr al-Islamy - Amal Fathullah Zarkasyi (Universitas Darussalam Gontor, 2009)
The principles of salafiah approach can be summarized into three distinguished characteristics: first is comprehension, second is authenticity or originality and not imitation (taqlid), while the last is improvement or progress and not conservatism. Salafiah is in fact not inconsistent with the progress and improvement, while their calling for returning to the original and main sources is approved by the religion and not in contradiction with the reality of Muslim. Moreover, it is a valid approach in achieving a better life in this world and hereafter. The objectives of salafiah are to purify the faith from the heresies (bid’ah), to educate Islamic personality, to open human mind to accept all the new in the fields of the experimental sciences, and to establish the faith from its sources which is far from the emerging narrow-minded religion sects recently. Finally, the salafist open widely to the experimental sciences, to the uses of scientific results, to the great invention in industrial sector and to the modern technology as they are very useful to support and sustain the Islamic teachings in the context of a more beautiful life with a less difficulties.